WAKAF SEBAGAI INSTRUMEN KEBIJAKAN PEMERINTAH UNTUK MENGATASI EKSTERNALITAS BARANG PUBLIK (PERSPEKTIF MAQASHID SYARI’AH) - Sancoyowati, Figuri (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2017)
Economic development bring externalities as a consequence of an economic activity in positive and negative side. An externality has beencaused by public goods whichis a goods that consumed by individual and will not effect to other in consumption of it. The issue of public goods is about a freeryder which caused in efficiency in government expenditures. Wakaf as a financial instument in Islam could bean alternatif to gainnationalin come that can solvean externality of public goods.